2013
DOI: 10.1590/s1806-37132013000400016
|View full text |Cite
|
Sign up to set email alerts
|

Transdiaphragmatic intercostal hernia: imaging aspects in three cases

Abstract: Transdiaphragmatic intercostal hernia is uncommon and mostly related to blunt or penetrating trauma. We report three similar cases of cough-induced transdiaphragmatic intercostal hernia, highlighting the anatomic findings obtained with different imaging modalities (radiography, ultrasonography, CT, and magnetic resonance) in each of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Macedo et al reported 3 cases of transdiaphragmatic intercostal hernia secondary to cough. 11 Contents for 2 of these were intestinal loops, and 1 of them was liver, and all of them were treated with thoracotomy. A review of 20 cases of spontaneous diaphragmatic rupture of diaphragm (variable intraabdominal hernial contents) by Losanoff et al were also repaired by thoracotomy as compared to our case, which was managed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…Macedo et al reported 3 cases of transdiaphragmatic intercostal hernia secondary to cough. 11 Contents for 2 of these were intestinal loops, and 1 of them was liver, and all of them were treated with thoracotomy. A review of 20 cases of spontaneous diaphragmatic rupture of diaphragm (variable intraabdominal hernial contents) by Losanoff et al were also repaired by thoracotomy as compared to our case, which was managed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…Macedo, et al [5] reported three cases of transdiaphragmatic intercostal hernia occurring in association with rib fractures. All patients underwent suture and mesh repair of the hernia as well as suture re-approximation of the fractured rib ends.…”
Section: Discussionmentioning
confidence: 99%
“…This can matter significantly for operative planning, and to understand what visceral or pleural contents are within the hernia sac. Others have reported cases with the intestine and liver within intercostal hernias, which clearly require a coexisting diaphragm hernia 2 4…”
Section: Discussionmentioning
confidence: 99%